(untitled) (Nigerian Journal of Physiological Sciences, 2019)
The excessive consumption of high cholesterol diet has been associated with an increased incidence of obesity. This is because obesity induced pathologies with high mortality, such as complications of dyslipidaemia, diabetes mellitus, arthritis, hypertension, myocardial infarction, and hepatocellular carcinoma. Although the associated, disease are enhanced by formation of oxidative stress, lipid peroxidation and hypercholesterolaemia. Magnesium chloride is found to be beneficial in a wide range of diseases. Magnesium is one of the most neglected mineral in human body. It is crucial for a healthy and lasting life. Magnesium is responsible for the activation of more than 300 enzymes in the body. The present study intends to determine the protective effect of magnesium chloride on liver enzyme and biomarker of oxidative stress in high fat diet fed rats. Twenty (20) adult Male Wistar rats weighing (100 – 150) grams randomly divided into three treatments and one control groups of five rats each (n = 5). Group I Normal control receive normal feed only for 6weeks, Group II received high fat diet only for 6weeks, Group III received high fat diet with 250 mg/kg for 6weeks of mgcl2 and Group IV received 500 mg/kg for 6weeks of MgCl2 respectively all treatments were administered via oral route, at the end of the sixth week rats were euthanized and blood samples were drawn from the heart by cardiac puncture and used to estimate oxidative stress biomarkers (Superoxide dismutase, Catalase and Glutathione peroxidase), lipid peroxidation biomarkers (Malondialdehyde) and liver enzymes. Analysis of variance and Turkey’s post hoc test were used to analyze the data obtained. In relation to the liver enzyme, the showed that there was a significant (p<0.05) decrease in value of AST, ALT and ALP in the group co-administered with the doses of the Magnesium chloride to compared to the control. For the oxidative stress biomarkers assessed, the results showed that there was significant decrease (P < 0.05) in the SOD, CAT and GPx level of the high fat diet fed groups, co-administered with 250 and 500 MgCl2, when compared with the high fat diet fed group only. Also, the lipid peroxidation shows significant (p<0.05) decrease in the groups administered the two doses of Magnesium chloride (250 and 500 mg/kg) respectively as compared to control. In relation to the liver enzyme, the showed that there were significant (p<0.05) changes in value of AST, ALT and ALP in the group co-administered with the two doses of the Magnesium chloride compared to the control. The result showed that high-fat diet induces ROS, dyslipidaemia and release of biological metabolite, as evidenced by the rise in oxidative stress and activities of liver enzymes. MgCl2 administration also protected the body against rise in the metabolites despite consumption of high-fat diet by the Wistar Rats.